Process Oriented Guided Inquiry Learning and Academic Achievement of Secondary School Economics Students in Ogun State - Oluwatosin, W. L.; Azeez, B. A. (NIU Journal of Social Sciences, 2020)
The study investigates Process Oriented Guided Inquiry Learning and academic achievement of secondary School economics students in Ogun State. The study employed quasi- experimental research designs. Four research questions and one hypothesis tested at 0.05 Alpha levels guided the study. A sample of two hundred and twenty (220) senior secondary economics students and twenty (25) economics teachers were drawn from the population through stratified random sampling technique. Four schools were randomly selected from four local government Areas and fifty-five SSS II students in each school were randomly assigned to the control and experimental groups. The data for the study was collected using a researcher- designed Questionnaire which was validated by experts in social sciences education and the Economics Achievement Test (EAT) that was adopted from Lagos State Ministry of Education 2 nd and 3 rd term unified examination held in 2013 & 2015 respectively. The reliability of the instrument was established (0.81) using Pearsonâ€™s Product Moment Correlation Analysis to establish the consistency of the instrument. Data collected were analysed using mean, standard deviation and t- test. The result shows that most of the students are of the opinion that learning economics is very interesting and therefore look forwards to economics classes. Thus, the students exhibited positive attitude towards teaching and learning economics. The findings also, shows that secondary school economics teachers opined that the students have attitude of often absenting themselves from school and also come late school.  Lastly, the result revealed that process oriented guided inquiry learning significantly affecst the performance in economics of secondary school students in the study area. The students exposed to PROGIL learning performed better (mean score =55.03) in economics when compared with the traditional teaching method (mean score=50.45). The two mean scores were statistically different in favor of POGIL, using t-test at 0.05 level of significance. Conclusively, POGIL as a teaching strategy enhances teamwork, critical thinking and problem solving skills in the students; which are pre-requisites for career growth and development. Based on the findings, there is a need for motivation to encourage studentsâ€™ regular attendance and early coming to school to have positive disposition to learning. The study recommends that POGIL as an instructional strategy must be encouraged in secondary economics classes as it was found to enhance academic achievement.The conventional method presently in use by secondary economics teachers can as well be improved upon or modified to improve secondary school studentsâ€™ academic achievement. Keywords: Economics, Process Enquiry Oriented Guided Learning, Team-work, Academic Achievement